THE REFORM OF CORRUPTION ERADICATION IN INDONESIA: THE PRISMATIC LAW IN THE RECENT CONTEXT - Akbar, Muhammad Fatahillah; Wicaksono, Dian Agung ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Thispaper aims to investigate the reform of corruption eradication in Indonesiafrom three crucial aspects: theform of the Corruption Eradication Commission (KPK), theformulation of corruption in material and formal aspects, and other additional support system such as asset recovery and the protection of justice collaborator and whistle blower. This paper is a normative-legal research where it dissects secondary data which includes statutory regulations, various legal documents, researches, and other references relevant to corruption eradication in Indonesia. KPK could be strengthened in particular aspects with changes in regards its design of authority and its relationship with other authorities in corruption eradication process